2018
DOI: 10.5897/err2018.3520
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Turkey and Germany Life Science teaching programs

Abstract: Comparative education studies within the perspective of globalization are seen as important studies, as they reveal the problems in education and show defective aspects of the systems applied in other countries. This way they improve the available system. The purpose of this research is to study the current curriculum of Life Science lesson within the context of four main elements comparatively. The Life Science lesson, which is assessed in the Social Studies course in many countries, is taught in Germany in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the literature, it has been determined that there are studies comparing the Life Science Curriculum between Türkiye and Germany (Baysal et al, 2018;Canbulat, 2018;Tekgöz, 2017), studies comparing the technological competencies of the curricula (Keskin, 2017), and studies comparing the Life Science Curriculum in Türkiye with the Russian "The World Around Us" Curriculum (Ütkür Güllühan & Guseinova, 2021). However, no research comparing the Life Science Curriculum in Türkiye and Azerbaijan has been found.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been determined that there are studies comparing the Life Science Curriculum between Türkiye and Germany (Baysal et al, 2018;Canbulat, 2018;Tekgöz, 2017), studies comparing the technological competencies of the curricula (Keskin, 2017), and studies comparing the Life Science Curriculum in Türkiye with the Russian "The World Around Us" Curriculum (Ütkür Güllühan & Guseinova, 2021). However, no research comparing the Life Science Curriculum in Türkiye and Azerbaijan has been found.…”
Section: Introductionmentioning
confidence: 99%